Potential role of endothelial progenitor cells in the pathophysiology of heart failure: clinical implications and perspectives. - Andreou, I; Tousoulis, D; Tentolouris, C; Antoniades, C; Stefanadis, C (2006)
Endothelial dysfunction is thought to play a major role in the development and clinical complications of heart failure. Endothelial progenitor cells (EPCs) have been shown to provide an endogenous repair mechanism to counteract detrimental risk factor-induced effects and replace dysfunctional endothelium. The number and in vitro function of EPCs is altered in patients with heart failure, as a result of its pathophysiological mechanisms. EPCs could represent a substitutional marker to guide preventive or therapeutic interventions in this disease. Enhancing the number and functional capacity of EPCs with targeted interventions may elicit functional improvement in individuals with heart failure. However, the exact role of EPCs in heart failure and their potential therapeutic implications still remain to be elucidated.